2017
DOI: 10.1159/000475759
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physicians in Rationing Cancer Care. Attitudes of German Oncologists

Abstract: Background: Against the background of limited resources, the rise in the cost of therapy as well as in the number of cancer patients fuels the discussion about the necessity to ration, i.e., setting limits to beneficial treatment for cost reasons. Recently, we presented the self-reported prevalence of bedside rationing among German oncologists. Here, we describe oncologists' views on cost containment strategies and their role therein. Methods: We performed an online survey including structured questions and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…As far as we are aware, this is the first qualitative study of oncologists’ views on the legitimacy of restrictions on access to new and expensive cancer drugs in a setting where national criteria-based priority setting is implemented and where a centralised drug review system is in place (but see [ 22 ]). This section considers key findings from the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as we are aware, this is the first qualitative study of oncologists’ views on the legitimacy of restrictions on access to new and expensive cancer drugs in a setting where national criteria-based priority setting is implemented and where a centralised drug review system is in place (but see [ 22 ]). This section considers key findings from the study.…”
Section: Discussionmentioning
confidence: 99%
“…The impact on doctor-patient relationship was a concern. Previous studies have concluded that limited drug funding and access has significant negative impact on oncologists’ practice [ 17 , 18 , 22 ]. Also, some of the participants experienced an unresolved ethical issue about whether to inform patients about drugs they did not think the patient would be able to pay for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neben Auch ist zu befürchten, dass sich ein Vergleich von Stationen oder Kliniken nicht nur auf die Qualität der Versorgung, sondern auch und primär auf Wirtschaftlichkeit (Profitabilität und Kosten) fokussieren und in dieser Sphäre einen Konkurrenzdruck um die "günstigste oder profitabelste Behandlung" weiter befeuern könnte. In einem Gesundheitssystem, welches ohnehin bereits unter hohem Kosten-und Ökonomisierungsdruck leidet (Strech et al 2008;Fernau et al 2017;Krause et al 2013), könnte dies einen weiteren Faktor zur Zuspitzung der Lage darstellen und durchaus negative Auswirkungen auf die Versorgungssituation selbst haben. Allerdings ist auch zu bemerken, dass ein Blick auf die Kosten von Behandlung im Rahmen eines eingepflegten Wirtschaftlichkeitsgebots stets erforderlich ist und z.…”
Section: Risiken Für Weitere Stakeholderunclassified
“…Only 29% reported being explicit about their rationing decision, if the patient did not know or inquire about the respective intervention. Further analysis of data of the same study including qualitative content analysis of free text answers shows that according to the perception of participating oncologists [20], cost considerations and negotiations in Germany are gaining in importance and consume considerable working time. Respondents not only reported negative effects of dealing with these issues on the job (72%), but also were concerned that the quality of care will be compromised by cost pressure.…”
Section: Assessing Benefit and Value Of Cancer Drugs - The Role Of Onmentioning
confidence: 99%